Healthy Food dan Penerimaan Pesan Pada Followers Akun Instagram @mixgreens.id - Rahajeng Kartika Wungu; Andre Noevi Rahmanto (Jurnal Komunikasi Massa, 2024)
Since the COVID-19 pandemic, our society has been trying to live a healthy life by exercising and eating healthy foods. Healthy food has finally become a new commodity in the culinary industry. Seeing the growing need for healthy food, Mixgreens is increasingly developing its business as a healthy food store in Solo. The rise of the trend of consuming healthy food encourages the author to find out the motivation of the community in consuming healthy food and how they view healthy food. This research finds out how Mixgreens' identity construction is based on Aristotle's rhetoric theory with the analysis of three proofs of persuasion; ethos, logos, pathos. In addition, this research also focuses on the acceptance of the @mixgreens.id Instagram account followers' messages to find out the acceptance of @mixgreens.id Instagram account followers with the basis of Stuart Hall's reception theory by grouping informants in dominant-hegemonic, negotiated, and oppositional positions (Hall, 2006). Information was obtained through the owner, content creator, and seven followers using the in-depth interview method. This research uses a sample of five categories of @mixgreens.id Instagram content. As a result, overall it can be interpreted that the content uploaded by @mixgreens.id Instagram account is a manifestation of the values held which is then communicated to the audience as Mixgreens identity. However, based on the results of the analysis, it is also concluded that the construction of Mixgreens' identity cannot be said to be good because there are incomplete elements and elements of rhetorical evidence in some content categories. The position of the majority of followers is dominant- hegemonic towards all content categories. This position is strongly influenced by age, background, level of education before being exposed to @mixgreens.id Instagram account content. This research also reveals that there is still a misunderstanding among audiences regarding the definition of healthy food.